Risk Factors for Testicular Atrophy in Children With Testicular Torsion Following Emergent Orchiopexy - Tian, Xiao-Mao; Tan, Xiao-Hui; Shi, Qin-Lin; Wen, Sheng; Lu, Peng; Liu, Xing; Li, Xu-Liang; He, Da-Wei; Lin, Tao; Wei, Guang-Hui (Frontiers in Pediatrics, 2020)
Objective: To analyze the risk factors for testicular atrophy (TA) in children with testicular torsion (TT) following emergent orchiopexy. Methods: Clinical data of patients with TT undergoing orchiopexy were retrospectively reviewed, including age at surgery, affected side, delayed surgery (12-24 hours and more than 24 hours), echogenicity of testicular parenchyma on ultrasonography (ETPU), testicular blood flow on Color Doppler ultrasonography (CDUS), surgical findings (intraoperative blood supply, the degree of torsion, and surgical approaches), and follow-up. The primary outcome was the rate of TA after orchiopexy. The secondary outcome was the testicular volume loss (TVL) between the affected testis and the contralateral. Results: A total of 113 patients were enrolled in this study with a median age of 11 years. The median follow-up was 21 months. Patients had a median TVL of 51.02% and 44 (38.94%) of them developed severe TA during follow-up. TA was significantly associated with age at surgery (P<0.0001), delayed surgery (P=0.0003), ETPU (P=0.0001), and intraoperative blood supply (P=0.0005). Multivariate logistic regression analysis showed that school-age children (OR=0.069, P<0.001) and puberty (OR=0.177, P=0.007) had a decreased risk of TA compared with preschool children, and that heterogeneous ETPU (OR=14.489, P=0.0279) and delayed surgery >24 h (OR=3.921, P=0.040) increased the risk of TA. Multivariate analysis demonstrated that ETPU (F=16.349, P<0.001) and delayed surgery (F=6.016, P=0.003) were independent risk factors for TVL. Conclusions: Age at surgery, delayed surgery, and ETPU may play a crucial role in predicting the TA in children with TT following emergent orchiopexy. Moreover, blood flow measured by CDUS could not predict the outcome properly.